The Impact of E-Learning on Motivation and Its Influence on the Interest in Studying Within the Campus Environment of Pelita Bangsa University in Cikarang - Indriana, Nina; Hisniati, Sally Badriya; Ridwan, Mohammad; Supiana, Supiana; Zaqiah, Qiqi Yuliati; Basri, Hasan (Budapest International Research and Critics University, 2025)
This study investigates the impact of e-learning and the campus environment on students' learning motivation and interest, as well as the mediating role of learning motivation. Using a quantitative causal methodology, the research involved 100 undergraduate students from Undiknas Denpasar, with data collected via questionnaires. Analysis was conducted using Microsoft Excel on responses from 130 students in various engineering disciplines through Google Forms. Findings reveal a significant positive effect of e-learning and the campus environment on learning motivation, with 46% of respondents highly satisfied with E-Learning (E-Campus UPB), 50% satisfied with campus facilities, 59% stating that media and facilities support their motivation, and 49% acknowledging the influence of these factors on their learning interest at the Faculty of Engineering UPB Cikarang.